Decolonialidades e identidades diaspóricas nos contos de Jamaica Kincaid - Bacchi, Bruna Stievano (2023)
This work's goal is to analise the short stories Girl, Blackness and Wingless, from the collectanea At the bottom of the river (1983) from the Caribbean writer Jamaica Kincaid. The short stories are narrated by the same narrator-protagonist, a girl whose age is not clear for the reader, but presumably between childhood and adolescence, who finds herself in a patriarchal setting with a colonial past. The themes presented in these short stories are connected with each other, such as colonialities that are part of the structure of current societies, and the legacies of colonization in places that have been through it, as Caribbean countries. The aim of this research is to demonstrate how the narratives question these processes, seeking to explain some of the colonialities that mainly affect women in these contexts. In this case, intersection of gender and race is brought into focus. The places and subjects are altered by the diaspora experience, thus the constitution of Caribbean diasporic identities is also examined. To do so, it seems necessary to offer a historical context in relation to the literary production of black Caribbean authors who live in the United States, and to examine patriarchal and colonial discourses through social, cultural and literary analyses. To do that, we used the theoretical basis of Homi Bhabha, Avtar Brah, Jana Evans Braziel, Divanize Carbonieri, Aimé Césaire, Kimberlé Crenshaw, Paul Gilroy, Ramón Grosfoguel, Leila Harris, María Lugones, Aníbal Quijano, among others.